The sea-coast (1) Destruction (2) Littoral drift (3) Protection - Wheeler, W. H. 1832-1915 (Longmans, Green, 1902)
This title deals with the effects of erosion and littoral drift on the English and continental coast-lines bordering the North Sea, and outlines protective measures including sea-walls and groynes.